SOCIAL CONSTRUCTION, INSTITUTIONALIZATION, AND PEACEMAKING CRIMINOLOGY APPROACH IN COUNTERING TERRORISM IN INDONESIA - Rahmat Amin Siregar; Adrianus Eliasta Meliala (UNIVERSITAS SEBELAS MARET (UNS), 2025)
The problem of counterterrorism in Indonesia continues to evolve, including institutional challenges and coordination effectiveness, terrorism funding, implementation of deradicalization efforts, and the political dimension of terrorism. It is important to discuss this phenomenon through a criminological approach that emphasizes the sociological paradigm. Previous studies have limitations in explaining social construction, institutional challenges, and offering Peacemaking Criminology approach in a more comprehensive and efficient counterterrorism effort in Indonesia. This research was conducted using a qualitative approach through thematic analysis of literature review on 57 previous studies. This research found four important findings. First, there are limited preventive detention clauses and communal or sectarian violence in Indonesia. Second, terrorism financing comes in various forms, poor coordination, and no comprehensive approach involving relevant stakeholders. Third, the complexity of efforts to deradicalize terrorism prisoners in correctional institutions. Fourth, the uncertainty in determining the status of terrorism due to political considerations. Peacemaking Criminology approach in this research offers a new solution to counter terrorism in Indonesia by targeting the root of radicalization through emancipative community development and discussing institutional challenges and ways to overcome them.